2013
DOI: 10.3109/0886022x.2013.846794
|View full text |Cite
|
Sign up to set email alerts
|

CKD is associated with recurrent ischemia but not with hemorrhagic transformation in acute ischemic stroke patients

Abstract: Background: We investigated the associations of Recurrent Ischemic Stroke (RIS) and Hemorrhagic Transformation (HT) with CKD in acute ischemic stroke patients. Method: The subjects were 160 patients, divided into two groups: with eGFR 560 mL/min/1.73 m 2 (CKD), with eGFR !60 mL/min/1.73 m 2 (without CKD). Results: Subjects having DM (p ¼ 0.018), CKD (p ¼ 0.025) and treated with ACEI/ARB (p ¼ 0.039) revealed association with RIS. Regression analysis disclosed only CKD (p ¼ 0.04). Carotid artery stenosis (p ¼ 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The present study demonstrated that low GFR was associated with increased risk of HT for AIS patients who did not receive thrombolysis therapy, which is in line with the result of two previous studies,[ 18 19 ] but slightly discriminating with the study of Micozkadioglu et al . [ 20 ] Nevertheless, it is worth mentioning that previous data possessed some unsolved restriction. In Lee et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study demonstrated that low GFR was associated with increased risk of HT for AIS patients who did not receive thrombolysis therapy, which is in line with the result of two previous studies,[ 18 19 ] but slightly discriminating with the study of Micozkadioglu et al . [ 20 ] Nevertheless, it is worth mentioning that previous data possessed some unsolved restriction. In Lee et al .…”
Section: Discussionmentioning
confidence: 99%
“…'s study, it was attributed to only conducting the univariate analysis for variable of interest. They did not performed multivariate regression analysis to eliminate the confounding factors for GFR variable (e.g., carotid artery disease,[ 20 ] serum calcium,[ 20 ] AF,[ 18 ] large infarct volume,[ 17 37 ] hypertension,[ 38 ] and albuminuria[ 39 ]), which are powerful impact factors on HT for AIS patients and could cover or even inverse the actually correlation between GFR and HT. In our study, the inclusion of patients without thrombolysis only represents the considerable strengths, and multivariate regression analysis was also performed to ensure the robustness of the conclusions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Micozkadioglu et al found a slight elevation in admission serum calcium level in 27 HT patients out of 160 stroke patients. 11 However, multivariate analysis was not performed and the percentage of patients treated with IVT was not mentioned. In patients with acute intracerebral hemorrhage, admission serum calcium level was also found to be negatively related to hematoma volume.…”
Section: Discussionmentioning
confidence: 99%